Morpho-agronomic characterization of native maize populations (Zea mays L.), province of Manabí, Ecuador - Murillo, Wilson; Sánchez-Mora, Fernando; Zambrano, Eddie; Pérez-Almeida, Iris; Ruilova, Favio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Ecuador is a country with a wide genetic diversity of maize and there are populations of native maize conserved by farmers that have not yet been characterized. These genetic resources could be conserved and used in plant breeding programs. The objective of this research was to characterize the morpho-agronomic diversity of 38 populations of native maize from the province of Manabí, Ecuador, using 19 quantitative and 11 qualitative morpho-agronomic descriptors. During the dry season of 2022 (July - December) at the Portoviejo Experimental Station of the National Institute of Agricultural Research (INIAP), plots of 8 m2 were established for each population of native maize, with 0.3 m between plants and 0.8 m between furrows and each furrow was 5 m long. Cluster analysis showed the formation of four groups, where the populations of hard kernels with large ears and soft kernels with short ears were separated into different groups. The quantitative variables ear height, panicle length, percentage of lodging, number of kernels per row and biomass of the inflorescence rachis recorded "D" indices of 0.75, showing themselves as discriminant variables in the formation of the groups, while the most discriminating qualitative variables were kernel type (χ2 = 49.09***, P= 0.742, V= 0.64), kernel color (χ2= 51.955***, P= 0.75, V=0.64), row arrangement (χ2= 18.11*, P=0.56, V=0.39), and kernel surface shape (χ2 = 20.52*, P=0.58, V=0.41). The native maize races identified were Candela, Cubano, Tuxpeño, Tusilla, and Uchima, observing significant genetic diversity in the populations studied. It was concluded that the characterized native maize populations were a valuable genetic resource for the conservation and use of this cereal.